2014
DOI: 10.1111/1346-8138.12657
|View full text |Cite
|
Sign up to set email alerts
|

First Japanese case of atypical progeroid syndrome/atypical Werner syndrome with heterozygous LMNA mutation

Abstract: Atypical progeroid syndrome (APS), including atypical Werner syndrome (AWS), is a progeroid syndrome involving heterozygous mutations in the LMNA gene encoding the nuclear protein lamin A/C. We report the first Japanese case of APS/AWS with a LMNA mutation (p.D300N). A 53-year-old Japanese man had a history of recurrent severe cardiovascular diseases as well as brain infarction and hemorrhages. Although our APS/AWS patient had overlapping features with Werner syndrome (WS), such as high-pitched voice, sclerode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 17 publications
1
18
2
Order By: Relevance
“…The D300 residue is located in the coiled-coil domain of lamin A, a region critical for lamin dimerization, suggesting that impaired lamin dimerization may be mainly associated with the pathogenesis of APS/ AWS. 3,19 Consistent with this finding, alternative splice forms of lamin A, such as progerin were not detected in APS/AWS fibroblasts with or without UVA irradiation in immunoblotting (Fig. 3b).…”
Section: Awssupporting
confidence: 82%
See 3 more Smart Citations
“…The D300 residue is located in the coiled-coil domain of lamin A, a region critical for lamin dimerization, suggesting that impaired lamin dimerization may be mainly associated with the pathogenesis of APS/ AWS. 3,19 Consistent with this finding, alternative splice forms of lamin A, such as progerin were not detected in APS/AWS fibroblasts with or without UVA irradiation in immunoblotting (Fig. 3b).…”
Section: Awssupporting
confidence: 82%
“…We previously reported that an abnormal nuclear morphology, increased aggregation of heterochromatin and decreased interchromatin granules in the nuclei of fibroblasts derived from patient with LMNA mutation were observed in immunofluorescence staining and electron microscopic analysis, suggesting that an abnormal nuclear morphology and chromatin disorganization might be associated with the pathogenesis of APS/AWS. In the current study, we showed that the protein levels of lamin A/C are lower in APS/AWS fibroblasts than in normal fibroblasts, suggesting that a reduced amount of lamin A/C may be associated with the abnormal nuclear morphology and abnormal distribution of heterochromatin in APS/AWS fibroblasts.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Consistently, levels of CBX1-Abs and CBX5-Abs were elevated in TIA and CI patients (Figures 3 and 4). In addition, there was an increase in the small aggregation of heterochromatin and a decrease in the level of interchromatin granules in the nuclei of fibroblasts from patients with atypical Werner syndrome (AWS), which is usually accompanied by disorders with multiple features resembling accelerated aging, mainly including vascular diseases such as aortosclerosis and DM [56, 57]. This suggests that abnormal nuclear morphology and chromatin disorganization may be associated with the pathogenesis of AWS/DM, and studies into the functional role of HP1 family members, particularly CBX5, which has diverse roles in the nucleus, including heterochromatin packaging and euchromatic gene regulation [52, 53], may be important.…”
Section: Discussionmentioning
confidence: 99%